How does home ownership affect migrants' sense of relative deprivation? An investigation based on field theory. (August 2022) - Liu, Danchen; Shen, Suyan; Shillair, Ruth; Li, Fang; Chen, Zhe
Abstract: Background: China is continuing to witness rising numbers of migrants (e.g., individuals migrating from rural to urban areas), and alongside this are the social restrictions and institutional barriers migrants face. Such restrictions and barriers are a consequence of the long-standing urban-rural dualist system and can create a sense of relative deprivation among migrants—that is, dissatisfaction when migrants perceive they are at a disadvantage compared with local residents of an area. Objective and method: Based on Pierre Bourdieu's field theory, the current study used data from the 2017 Chinese General Social Survey ( N  = 1849) to explore the mechanism through which migrants' home ownership or non-ownership in the migration process affects their sense of relative deprivation. To do so, a ranked regression and parallel multiple mediation model were developed. Additionally, a heterogeneity analysis was conducted to account for the region in which migrants lived and their age. Results: The results revealed that home ownership significantly reduced migrants' relative deprivation. Moreover, the perception of economic and symbolic capital was found to play a role in the effects of wealth and class, respectively. From the heterogeneity analysis, the direct and mediated effects of housing attributes on migrants' relative deprivation were more significant for migrants in the eastern versus central and western regions of China, as well as among new-versus older-generation migrants. Conclusion: To improve the feasibility of home ownership among migrants and, thus, alleviate their relative deprivation in the inflow area, relevant policies (e.g., improving the housing system pathway) should be developed and implemented. Highlights: Home owners have a lower sense of relative deprivation than renters in migration. Home ownership reduces relative deprivation through economic and symbolic capital perceptions. Migrants in Eastern China were more affected as well as the younger generation.